Artificial Activation of Escherichia coli mazEF and hipBA Toxin–Antitoxin Systems by Antisense Peptide Nucleic Acids as an Antibacterial Strategy - Równicki, Marcin; Pieńko, Tomasz; Czarnecki, Jakub; Kolanowska, Monika; Bartosik, Dariusz; Trylska, Joanna (Frontiers in Microbiology, 2018)
The search for new, non-standard targets is currently a high priority in the design of new antibacterial compounds. Bacterial toxin-antitoxin systems (TAs) are genetic modules that encode a toxin protein that causes growth arrest by interfering with essential cellular processes, and a cognate antitoxin, which neutralizes the toxin activity. TAs have no human analogues, are highly abundant in bacterial genomes, and therefore represent attractive alternative targets for antimicrobial drugs. This study demonstrates how artificial activation of Escherichia coli mazEF and hipBA toxin-antitoxin systems using sequence-specific antisense peptide nucleic acid oligomers is an innovative antibacterial strategy. The growth arrest observed in E. coli resulted from the inhibition of translation of the antitoxins by the antisense oligomers. Furthermore, two other targets, related to the activities of mazEF and hipBA, were identified as promising sites of action for antibacterials. These results show that TAs are susceptible to sequence-specific antisense agents and provide a proof-of-concept for their further exploitation in antimicrobial strategies.